LINKING THE MESOPROTEROZOIC BELT-PURCELL AND UDZHA BASINS ACROSS THE WEST LAURENTIA-SIBERIA CONNECTION - Sears J.W.; Price R.A.; Khudoley A.K. (My University, 2004)
Paleogeographic reconstruction of the northern Siberian craton against southwestern Laurentia, in accordance with paleomagnetic data, basement piercing points, and the best fit of the rift margins, aligns Mesoproterozoic dike and sill swarms in northeast Siberia with correlative ones in Montana and Wyoming. It also juxtaposes the Mesoproterozoic Belt-Purcell basin of west Laurentia against the Mesoproterozoic Udzha basin of the northern Siberian craton. We review the veracity of this hypothetical Belt-Purcell–Udzha basin as a test of our Siberia–west Laurentia reconstruction. Various elements of the structural framework of the basins are closely aligned in the reconstruction. The Udzha trough is aligned with the St. Mary–Moyie fault zone and Vulcan basement structure of southwestern Canada. The Khastakh trough is aligned with the Helena embayment of central Montana. Parts of the Belt-Purcell Supergroup appear to correlate with parts of the Riphean section in northeastern Siberia. However, the Siberian section appears to be much thinner than the Belt-Purcell section, and precise correlation is not possible with present stratigraphic and geochronological data. The reconstruction leads to the prediction that the Udzha rift channeled sediment from a cratonic pediment into the delta and alluvial fan complex in the deep Belt-Purcell rift-basin. Distributary channels may have shifted within the Udzha basin to feed shifting depocenters in the Belt-Purcell basin. Details of age and tectonic evolution for the Udzha basin are less clear than for the Belt-Purcell basin, but we outline specific geological relationships predicted by the reconstruction model, and suggest tests for future research.
Keywords: Laurentia; Siberia; Mesoproterozoic; Paleogeography; Belt-Purcell basin; Precambrian::Proterozoic::Mesoproterozoic; Докембрий::Протерозой::Мезопротерозойская